Coupling calculation and analysis of three‐dimensional temperature and fluid field for high‐power high‐speed permanent magnet machine. Issue 6 (20th May 2019) - Wang, Tianyu; Zhang, Yue; Wen, Fuqiang; Gerada, Chris; Liu, Guangwei; Rui, Dai; Zerun, Wang
Abstract : In order to accurately estimate the temperature rise for high‐power high‐speed permanent magnet machines (HSPMMs), a novel temperature calculation method considering the non‐linear variation of material properties with temperature is proposed based on multi‐physics co‐simulation analysis. According to the theory of computational fluid dynamics and heat transfer, the computation model of fluid–solid–heat coupling heat transfer is established, and the coupled field is calculated using finite volume method with fundamental assumptions and corresponding boundary conditions. With the influences from temperature gradient and water flow rate considered, the heat transfer coefficients of water pipe surfaces are obtained by the application of the inverse iteration method. Thus, HSPMM temperature and fluid field can be simulated numerically by the finite volume methods, while the spatial temperature distributions for the machine main components are analysed in this study. The 1.12 MW, 18, 000 rpm HSPMM is prototyped with experiments conducted on it, while the test data are then compared with the calculated results, which validate the correctness of the solution method of the coupled field.